Antihyperlipidemic effect of Ficus dalhousiae miq. stem bark on Triton WR-1339 and high fat diet-induced hyperlipidemic rats - Surendran Surya; Ravindrakurup Arun Kumar; Betty Carla; Christudas Sunil (Bulletin of Faculty of Pharmacy Cairo University, 2017)
Ficus dalhousiae stem bark is used to treat cancer and hyperlipidemia in folklore practices. F. dalhousiae stem bark methanolic extract (250 and 500 mg/kg b. wt.) was evaluated for antihyperlipidemic activity in Triton WR-1339 and high fat diet-induced hyperlipidemic rats. F. dalhousiae extract significantly (P ⩽ 0.005) alter the serum TC, TG, LDL-C and HDL-C levels to near normal in Triton WR-1339 and high fat diet-induced hyperlipidemic rats. The liver total cholesterol and triglycerides were also significantly reduced after treatment with 250 and 500 mg/kg of F. dalhousiae. The result of this study indicates that F. dalhousiae has a significant potential to use as a natural antihyperlipidemic agent.